Online Games between Risk and Potential: A Study of Learning Motivation and Digital Science Literacy - Maria Hanifah; Nazri Adlani (Lembaga Yasin AlSys, 2026)
The phenomenon of online gaming addiction among sixth-grade students at MIN 1 Aceh Tengah has become an important issue because it is related to students’ learning motivation and digital science literacy. The tendency to play online games is considered to affect enthusiasm, focus, and learning habits, which are influenced by both internal and external factors. This study aimed to analyze the impact of online gaming addiction on students’ learning motivation and digital science literacy, as well as to identify internal and external factors that influence the relationship between online gaming activities and learning motivation. This study used a descriptive qualitative approach with research subjects consisting of teachers and sixth-grade students. Data were collected through observation, interviews, and documentation, and were then analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results showed that online gaming addiction affected students’ learning motivation in various ways. Students who played without self-control and received limited parental supervision experienced a decline in concentration and learning enthusiasm, whereas students who were able to manage their time and received parental support showed increased motivation, perseverance, and critical thinking skills. The development of digital science literacy was evident in the use of gadgets to search for science materials through Google, watch learning content through YouTube, and ask for answers to science questions through the Gemini application. Internal factors influencing this relationship included self-control, interest, and learning habits, whereas external factors included parental supervision, peer environment, and digital facilities. The conclusion of this study confirms that balanced management of online gaming activities, accompanied by self-control and parental supervision, plays an important role in maintaining learning motivation and supporting the development of students’ digital science literacy.